Documenting acousmatic music interpretation: a developmental framework based on cross self-confrontations. Issue 3 (2nd September 2021) - Boutard, Guillaume; Féron, François-Xavier
ABSTRACT: The investigation of acousmatic music interpretation as a distinct activity from composition calls for the investigation of appropriate documentation frameworks. This paper investigates the relevance of cross self-confrontations to capture all dimensions of interpretation of acousmatic music from a dialogical and developmental perspective. This study is the second phase of the project Interpretation Spatiale des Musiques Electroacoustiques (ISME), following a theoretical investigation of acousmatic music interpretation. It is based on the automated re-enactment of several performances conducted during an acousmatic interpretation workshop and masterclass at LaBRI-SCRIME in 2015. The analysis presents the practical and theoretical relevance of the framework in relation to the dimensions of acousmatic interpretations conceptualized during the first phase of the project based on semi-structured interviews.